Experimental study of pure steam and steam–air condensation over a vertical corrugated tube. (November 2018) - Fan, Guangming; Tong, Pan; Sun, Zhongning; Chen, Yitung
Abstract: The natural convection condensation heat transfer outside the vertical smooth tube and corrugated tube was experimentally investigated in pure steam and steam–air conditions, respectively. The aim of the research was to evaluate the heat removal capacity of the corrugated tube through comparing with the test results of the smooth tube. In the experiment, a corrugated tube was tested, the bulk temperature and the wall temperature of crest and trough were measured in detail. The result of the temperature measurement demonstrated that the difference of heat transfer characteristics at the crest and trough is not significant. In the pure steam condition, the influence of subcooling on condensation heat transfer coefficient of the corrugated tube is reduced. Comparing with the smooth tube, the condensation heat transfer coefficient of the corrugated tube has been increased for more than 10%. In the steam–air test condition, the condensation heat transfer coefficients have been obtained for the air mass fraction from 0.1 to 0.95 and the total pressure from 0.2 MPa to 0.5 MPa. The corrugated tube shows a slight enhancement with an average increase of condensing heat transfer coefficient about 10%. Highlights: Steam–air mixtures condensation outside a corrugated tube is conducted. The difference of heat transfer characteristics at the crest and trough is compared. The corrugated tube weakens the impact of subcooling on the coefficient of condensing heat transfer. Compared with smooth tube, the corrugated tube enhances the steam-air condensation heat transfer process slightly.